AN INTRODUCTION TO THE CONCEPT OF FUZZY MULTISET BITOPOLOGY - Dauda, Haruna; Alkali, Alhaji Jlbril; Shagari, Mohammed Shehu (FUDMA Journal of Sciences, 2025)
In this paper, we introduce the concept of fuzzy multiset bitopological spaces. Moreover, the notions of fuzzy submultiset of bitopological space, union, intersection and Hausdorf fuzzy multiset bitopology are studied and presented. The importance of this approach is that, the class of fuzzy multiset bitopological spaces is wider and more general than the class of classical bitopological spaces.